Assessing eccentric hamstring strength using the nordbord: between-session reliability and interlimb asymmetries in professional soccer players - Bishop, C.; Manuel, J.; Drury, B.; Beato, M.; Turner, A. (The Journal of Strength and Conditioning Research, 2022)
The aims of the current study were to (a) determine between-session reliability of peak force during the Nordic hamstring exercise (NHE) in professional soccer players during the preseason and (b) determine the subsequent magnitude and direction of peak force asymmetry from the NHE between all test sessions. The NHE was used as a weekly monitoring tool in 14 professional soccer players, throughout a 6-week pre-season period to record peak force from the NordBord device (in Newtons—N) across an average of 6 repetitions for the dominant and nondominant limbs. The first 2 weeks were used as familiarization sessions, with 4 data collection sessions thereafter. When considering relative reliability, intraclass correlation coefficients (ICCs) showed moderate levels of between-session reliability across the 4 weeks on both limbs (dominant = 0.54-0.73 and nondominant = 0.68-0.73) and for the sum total (0.69-0.73). For absolute reliability, both limbs showed coefficient of variation (CV) values <10% across all 4 weeks, with the exception of the dominant limb between sessions 1-2 (10.06%). When determining systematic bias, no meaningful changes were evident in peak force on either limb (g = -0.59 to 0.40) or for the magnitude of asymmetry (g = -0.24 to 0.35). However, when assessing consistency in the direction of asymmetry, levels of agreement ranged from 43 to 57% across the data collection period, indicating substantial variation in the superior performing limb from session to session. The findings from this study indicate that 2 familiarization sessions is enough to elicit reliable peak force data during the NHE in professional soccer players during preseason, despite a very small learning effect across the testing period.